Transcriptomic analysis of barley plant responses to cold stress - Wu, Jing (2010)
Previous molecular and genomic studies have shown that several group genes in Arabidopsis with various functions are induced by cold stresses, and that various transcription factors are involved in the regulation of stress-inducible genes which contribute to an increase in cold tolerance. Here, we present the results of transcriptome analysis indicating the existence of genes of potential importance to cold stress and multiple low-temperature regulatory pathways in addition to the cold response pathway in barley.